2016
DOI: 10.4187/respcare.04335
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Variations in Use of Prescription Medicines for COPD: A Register-Based Study

Abstract: BACKGROUND: The purpose of this study was to examine socioeconomic variations in the use of prescription medicines among elderly subjects with COPD. METHODS: Data from the Danish national administrative registers were used. The study population included 1,365 individuals >60 y old residing in the Municipality of Copenhagen and diagnosed with COPD in a hospital setting in 2007. Logistic regression analysis was applied to examine the associations between the use of all prescription medicines for obstructive pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(15 reference statements)
3
1
0
Order By: Relevance
“…Our finding that lower income is associated with nonuse agrees with two previous studies [26,27]. A Danish registerbased study examining socioeconomic variations in use of maintenance medications in 1365 COPD patients >60 years old showing a lower risk of non-use among more affluent patients [26], and a US study showing lower use of LAMA among low-income COPD patients 55 years old (23). We also found lower income to be associated with poor adherence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that lower income is associated with nonuse agrees with two previous studies [26,27]. A Danish registerbased study examining socioeconomic variations in use of maintenance medications in 1365 COPD patients >60 years old showing a lower risk of non-use among more affluent patients [26], and a US study showing lower use of LAMA among low-income COPD patients 55 years old (23). We also found lower income to be associated with poor adherence.…”
Section: Discussionsupporting
confidence: 91%
“…The authors did not have information on diagnosis status, but in a related study they observed a higher proportion of individuals with high education receiving no treatment the year leading up to baseline [25], which could be indicative of underdiagnosis. Our finding that lower income is associated with nonuse agrees with two previous studies [26,27]. A Danish registerbased study examining socioeconomic variations in use of maintenance medications in 1365 COPD patients >60 years old showing a lower risk of non-use among more affluent patients [26], and a US study showing lower use of LAMA among low-income COPD patients 55 years old (23).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many patients received no treatment despite experiencing symptoms, and among those on treatment most received ICS irrespective of the severity of airflow limitation, asthma diagnosis, and exacerbation history. Several other studies have reported undertreatment with bronchodilators in comparison with ICS [9,13], or a majority of patients receiving LABA/ICS without LAMA [16]. Rather few studies have investigated temporal change in treatment patterns, but our results of decreased proportions of patients with sole ICS treatment or no maintenance treatment at all over time are consistent with a study of COPD patients in UK primary care [12].…”
Section: Discussionsupporting
confidence: 87%